A CRISPR-Cas12a-based specific enhancer for more sensitive detection of SARS-CoV-2 infection - Weiren Huang; Lei Yu; Donghua Wen; Dong Wei; Yangyang Sun; Huailong Zhao; Yu Ye; Wei Chen; Yongqiang Zhu; Lijun Wang; Li Wang; Wenjuan Wu; et al. (EBioMedicine, 2020)
Background: Real-time reverse transcription-PCR (rRT-PCR) has been the most effective and widely implemented diagnostic technology since the beginning of the COVID-19 pandemic. However, fuzzy rRT-PCR readouts with high Ct values are frequently encountered, resulting in uncertainty in diagnosis. Methods: A Specific Enhancer for PCR-amplified Nucleic Acid (SENA) was developed based on the Cas12a trans-cleavage activity, which is specifically triggered by the rRT-PCR amplicons of the SARS-CoV-2 Orf1ab (O) and N fragments. SENA was first characterized to determine its sensitivity and specificity, using a systematic titration experiment with pure SARS-CoV-2 RNA standards, and was then verified in several hospitals, employing a couple of commercial rRT-PCR kits and testing various clinical specimens under different scenarios. Findings: The ratio (10 min/5 min) of fluorescence change (FC) with mixed SENA reaction (mix-FCratio) was defined for quantitative analysis of target O and N genes, and the Limit of Detection (LoD) of mix-FCratio with 95% confidence interval was 1.2≤1.6≤2.1. Totally, 295 clinical specimens were analyzed, among which 21 uncertain rRT-PCR cases as well as 4 false negative and 2 false positive samples were characterized by SENA and further verified by next-generation sequencing (NGS). The cut-off values for mix-FCratio were determined as 1.145 for positive and 1.068 for negative. Interpretation: SENA increases both the sensitivity and the specificity of rRT-PCR, solving the uncertainty problem in COVID-19 diagnosis and thus providing a simple and low-cost companion diagnosis for combating the pandemic. Funding: Detailed funding information is available at the end of the manuscript.